Mapping the 'Implicated Subject': A Reading of Plestia Alaqad's The Eyes of Gaza. - Thomas, Ashna; Mathew, Minu Mary (Teresian Journal of English Studies)
The present age is marked by an unprecedented rate of forced migration owing to growing geopolitical tensions. Conflict-induced displacement produces subjects who resist being fixed within the category of ‘refugee,’ revealing tensions between lived experience and imposed identity. The attempt to escape the refugee label comes at a cost. This paper examines The Eyes of Gaza by Plestia Alaqad to show how the victim and bystander notions that continue to dominate the cultural imaginary need to be reshaped by drawing on Michael Rothberg’s concept of the implicated subject. The Eyes of Gaza is a series of diary extracts spanning the days in the life of the author and her community since the October 7 attacks in 2023, in which she offers a glimpse of her life before the attacks, the escalation to genocide, and her continuous displacement until she takes refuge in Australia. Alaqad questions her subject position, as it shifts between observer and displaced and vice versa. Rothberg’s theory of implicated subjectivity reconceptualises traditional subject positions in the context of forced displacement, fostering a shared sense of responsibility among readers. Implicated subjectivity emerges through the author’s reflexive narration, enabling a critical distance fromher community without relinquishing affective proximity, while ‘complicity’ is ultimately activated at the level of readership through mediated witnessing and ethical recognition. In doing so, Alaqad underscores the necessity of rethinking ethical responsibility, particularly for readers who remain distant observers of genocidal violence.